The Effect of a Proposed Training Program Using a Short Ball On Developing Motor Response Speed in Young Table Tennis Players - Hammadi, Hamdullah (Indonesian Journal Publisher, 2025)
Motor response speed is one of the basic abilities that determine a player's proficiency in table tennis, as the nature of the game requires quick decision-making and reaction in rapidly changing situations. This research aims to design a training program using a short ball and analyze its impact on developing motor response speed among youth table tennis players (17–19 years old). The researcher adopted an experimental approach using a single-group approach with pre- and post-tests. The sample included 12 players from a youth league club. The training program was implemented over eight weeks, with three sessions per week. Field-approved response speed tests were used, in addition to video recording and analysis of performance. The training sessions included exercises based on the use of a short ball in various positions and rapidly changing scenarios, with the aim of stimulating the motor nervous system to respond immediately. The results showed a significant improvement in the post-test results compared to the pre-test results, demonstrating the effectiveness of the proposed training program. The research highlights the importance of customizing training programs according to the specificity of the targeted skill and the nature of the competitive situation, and recommends implementing the program in youth training centers to develop response speed skills. The researcher also recommends conducting future studies on different age groups and incorporating new training methods such as virtual reality to enhance training effectiveness.